Hikmah Dalam Perspektif Pembinaan Hukum Islam - Moh Hasyim (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2004)
This study aims to examine the concept of wisdom in Islamic law and its implications for the formulation of fair and contextual law. The method used is normative juridical research with a conceptual approach and analysis of the main sources of Islamic law, such as the Qur'an, Hadith, and the thoughts of scholars. The results of the study show that the wisdom of Islamic law does not only refer to discretion, but also to the purpose of the law (maqāṣid al-sharī'ah) which emphasizes the interests of the community. The principle of wisdom plays a role in the flexibility of Islamic law so that it can be applied in accordance with the times without losing the essence of sharia. Therefore, in the development of Islamic law, an approach is needed that balances normative texts and social needs in order to create a more responsive and equitable legal system.